Eight-element liquid crystal based 32 GHz phased array antenna with improved time response. (26th November 2021) - Nobles, Jason E; Smiley, K; Bueno Baques, D; Economou, E; Herman, Jakub; Harward, Ian; Glushchenko, Anatoliy; Camley, Robert E; Celinski, Z
Abstract: Phased array radar systems are used for a wide variety of applications including the precise tracking of airborne craft for air traffic control and providing accurate atmospheric condition information important in weather forecasting. Reducing the cost and size of these radar systems will open new fields to the use of this technology. Using phase control implemented through liquid crystal materials we have created a compact, phased array radar system operating in the microwave range. We report on the construction and testing of a linear, eight element phased array antenna system operating at 32 GHz with element phase controlled by a dual frequency nematic liquid crystal media used as a tunable dielectric. The system was designed using CST Design Studios and Ansys HFSS software. Dual frequency liquid crystals are used to improve beam steering response times. We demonstrate 42 millisecond beam switching times, defined as the time to change the beam focus from one point to another point, controllable beam formation, and beam steering profiles consistent with analytical results and simulation models. The device footprint is a square with sides 9.5 cm long and a thickness less than 2.5 mm. Such a module is easily stackable to create an 8 × 8 phased array system. Our design incorporates a modular construction using PCB for the antennas and input circuitry and a liquid crystal phase control cell with microwave glass substrates. This design simplifies design, construction, and testing as compared to on-glass designs. The device shows an improvement in point-to-point scanning speeds by a factor of 3 as compared to similar liquid crystal based devices and provides continuously variable tuning. Such a device can be used in a system for reduced visibility, directional range finding suitable for automobile collision avoidance systems and rotary wing aircraft landing aids.